Social Nerworks Dangers: How to educate our childs in cibersecurity - Astorga-Aguilar, Cristel (2019)
This research aims to analyze the state of the art in the country of the knowledge of dangers of online social networks and how to protect minors through good cybersecurity practices.Through a bibliographic review, different topics related to the management of social networks and dangers young people in Costa Rica are exposed to. Security and privacy terms are evaluated, as well as the role of parents, and some elements of Cybersecurity of the most popular Social Networks among underage people. Among the most important findings, it was determined that the greatest dangers of social networks for minors are harassment, cyberbullying, grooming, sexting and addiction, which, without an adequate education in Cybersecurity, make children vulnerable. The most popular social networks online among children and adolescents are Facebook, Instragram, Whatsapp, and SnapChat, and each one is governed by a series of conditions; these media also offer a series of tools to ensure privacy and data security, but they must be configured and this is basically what we know as Cybersecurity. Educating children in cybersecurity is a new challenge for parents: they must know and be prepared to teach their children on how to protect themselves from these new dangers.